"We've done it!" - [S.P.] (Truth ?, 1909)
Scholarly notes may be added at a later date.
Truth Christmas Number, December 25, 1909
1 print : col.
Keywords: Caricatures; Cartoons; David Drage & Sons; Great Britain -- Politics and government -- 1901-1936